D-band transdirectional coupler employing an interdigital capacitor structure in 55-nm BiCMOS - Simionato, Elígia; Serrano, Ariana Lacorte Caniato; Rehder, Gustavo Pamplona; Rosa, Guilherme Simon da; Penchel, Rafael Abrantes; Ferrari, Philippe (IEEE, 2026)
This work presents the first demonstration of a transdirectional (TRD) coupler operating at sub-THz frequencies. TRD couplers are particularly useful in active circuits due to their intrinsic DC blocking behavior, which is exclusive to this type of coupler. Despite the existence of techniques that enable high-frequency designs, no TRD coupler design has yet been demonstrated for frequencies above 30 GHz. This work therefore aims to demonstrate a TRD coupler operating within the D-band (110 GHz to 170 GHz), using an interdigital capacitor structure and considering a 55-nm BiCMOS technology. The proposed coupler's performance was verified through full-wave electromagnetic simulation and compared to other TRD designs from the literature. The proposed coupler occupies the smallest area and demonstrates comparable or superior performance across various parameters, with the exception of its quadrature behavior.
Acoplador transdirecional na banda D utilizando uma estrutura de capacitor interdigital em tecnologia BiCMOS de 55 nm
Keywords: Capacitadores; Simulação (Computadores); Circuitos integrados